A brief history of rock 'n' roll - Johnstone, Nick 1970- (Carroll & Graf, 2007)
Rock and Roll was born in 1956. In that year, Elvis released "Heartbreak Hotel"; Chuck Berry sang "Roll Over Beethoven"; Little Richard blurred the boundary with "Tutti Fruitti"; Janis Martin sang for women with "Drugstore Rock and Roll", while pop music hit the big screen with "Rock Around the Clock". In one year the youth quake went overground. Music journalist Nick Johnstone charts the events of this turning point and the origins of rock and roll, showing how the DNA fused in that one burst of creativity persisted for the next 50 years.